The economic burden of atopic dermatitis in Romania: a broad perspective - Nicolescu, Alin Codruț; Strilciuc, Stefan; Lăpădatu, Rozalina; Grad, Diana-Alecsandra; Vlădescu, Cristian; Olteanu, Rodica (Frontiers in Public Health, 2025)
IntroductionAtopic dermatitis (AD), a common dermatological condition, is often associated with significant economic and social burdens. Despite extensive studies globally, there is a gap in understanding the impact of this condition in Romania. This study evaluated the economic burden of AD in Romania, considering both direct and indirect costs.Materials and methodsA cost of illness study, conducted from a broad perspective, considering 2022 as a reference, using top-down and bottom-up approaches and retrospective and prospective data sources was used to assess direct medical costs (treatments, medical services, hospitalizations), direct non-medical costs (associated costs due to transportation, accommodation), and indirect costs (productivity losses) across four costing scenarios.ResultsIn 2022, the total cost of atopic dermatitis in Romania was €29,810,077.2 for adult patients and €133,635,535.2 for pediatric patients, based on a prevalence-based approach, and €5,529,867.8 for adults and €53,175,049.1 for pediatric AD patients when using an incidence-based approach. Medical costs had the highest attributable share of the AD cost for adult patients while productivity costs (inquired by caregivers) had the highest share for pediatric AD patients in both approaches. The overall average annual cost per patient ranged, depending on the scenarios, between €284.72 and €1,045 for adult AD patients and between €293.73 and €9,558.52 for pediatric AD patients.DiscussionOur results show the increased burden among pediatric AD patients emphasizing the need that future policy interventions should be tailored according the patients’ age.